Zircon-Reidite in Prismatine Granulite from Waldheim/Saxony - Thomas, Rainer; Davidson, Paul; Rericha, Adolf (Current Research Progress in Physical Science Vol. 9, 2025)
Reidite is the high-pressure scheelite-type polymorph of zircon. According to Raman spectroscopic studies these zircons often contain remnants of the reidite. The transformation of zircon to reidite is reconstructive in nature and is connected with a density change of about 9%). According to microscopic and Raman spectroscopic-based studies of prismatine rock from Waldheim/Saxony, spherical zircon crystals with remnants of reidite and monoclinic ZrO2 were observed. The proof of reidite in a metamorphic rock is the first one because up to now, reidite was found only in impact structures. The rock and crystal samples were collected by the first author in 1967 from the exposure near the Waldheim railway station. Nearly all minerals (garnet, corundum, quartz, prismatine, feldspar, sillimanite) of the prismatine rock contain randomly distributed spherical zircon crystals with a very smoothed surface and with dimensions between 10 to 50 µm. The frequency of these grains is with about 180 spheres/cm3 not high. Results show that in the Raman spectra of the spherical zircon crystals in the prismatine rock from Waldheim bands characteristic of reidite have often been seen. It has been found that at very high pressures zircon break down into oxides. Together with the finding of coesite and stishovite, reidite and monocline ZrO2 in zircon give clear hints that such phases arrived very rapidly from very great depths into the higher crustal level (90 km) via supercritical fluid/melt. In conclusion, these observations throw new light on the genesis of the HP-HT prismatine rock from Waldheim. It has been interpreted that the spherical crystals as hints of a supercritical phase coming from very great depths, very rapidly (possibly together with boron) into the crystallization level of prismatine.